Isothermal and non-isothermal crystallization Kinetic behavior of zinc-ferrite formation in theLow temperature flow injection co-precipitation synthesis reactor - Sasito, Edie; Soegijono, Bambang; Manaf, Azwar (Jurnal Spektra, 2013)
The kinetic behavior of zinc -ferrite crystallization process has been studied by co-precipitation of chlorine salt and alkaline solution. Either the parameter of temperature rate variation, pH previous of reactant and pH alkaline solution results non isothermal process was described by Ozawa equation,. There are significantly deferent in the taking both isothermal and non isothermal data. In the non- isothermal there are just oneexperiment can be sufficiency to reveal any crystal forming parameters but in the isothermal needs several different temperature experiments to reveals the parameter of crystal forming . In this research have be done one time non -isothermal experiment at means temperature 40 0C with temperature increase from 49 0C to 530C, and four time isothermal experiments at means temperature 60 0C,70 0C and 80 0C respectively. The sampling of experiment data have be done effectively using pH real- time video data logger. As a result the energy forming of the zinc ferrite both isothermal and non-isothermal are -4.27kcal/.mol,5.61kcal/mol respectively. The other kinetic parameter of crystallization and crystalline mechanism of both processes will be discussed.Keywords:co-precipitation, zinc-ferrite, non-isothermal process, crystallization, crystalline mechanism, data logger, kinetic behavior, flow injection co-precipitation synthesis.